2018
DOI: 10.5935/1981-2965.20180015
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da qualidade microbiológica, físico-química e química de polpas de açaí (Euterpe oleracea Mart) pasteurizadas congeladas comercializadas em Aracaju-SE

Abstract: Avaliação da qualidade microbiológica, físico-química e química de polpas de açaí (Euterpe oleracea Mart) pasteurizadas congeladas comercializadas em Aracaju-SE Evaluation of the microbiological, physicochemical and chemical quality of frozen pasteurized açaí pulps (Euterpe oleracea Mart

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
3
2
2
Order By: Relevance
“…[37] says that the presence of fungi in food above the maximum recommended by the legislation can compromise their food safety, since there are species of fungi that have a deteriorating or pathogenic action due to the production of myco toxins in the food. In a study on the microbiological quality assessment of frozen pasteurized açaí pulp (Euterpe oleracea Mart) type C. Almico et al (2018) [24] found similar results with the study, the samples did not show fungi and yeast contamination above that legislation allows, since the authors find results of molds that ranged between 4.99x10 2 CFU/g, which are similar with the present study. In a study on the microbiological quality of industrialized acai.…”
Section: Microbiological Analysissupporting
confidence: 91%
See 3 more Smart Citations
“…[37] says that the presence of fungi in food above the maximum recommended by the legislation can compromise their food safety, since there are species of fungi that have a deteriorating or pathogenic action due to the production of myco toxins in the food. In a study on the microbiological quality assessment of frozen pasteurized açaí pulp (Euterpe oleracea Mart) type C. Almico et al (2018) [24] found similar results with the study, the samples did not show fungi and yeast contamination above that legislation allows, since the authors find results of molds that ranged between 4.99x10 2 CFU/g, which are similar with the present study. In a study on the microbiological quality of industrialized acai.…”
Section: Microbiological Analysissupporting
confidence: 91%
“…Comparing to the study by Aquino et al (2014) [23], where they studied the physical-chemical and microbiological evaluation of açaí (Euterpe oleracea), similar results of pH were found, values ranging from 4.27 ± 0.73 to 5.73 ± 0.01. In our study, the results were higher than values found by Almico et al (2018) [24], these authors found value of pH ranged 4.29 ± 0.15 to 4.12 ± 0.35. The pH of food is a determining factor in the multiplication of microorganismsmost of the deteriorants multiply optimally at pH close to neutrality (6.6 to 7.5) [25].…”
Section: Physicochemical Analysiscontrasting
confidence: 88%
See 2 more Smart Citations
“…No estudo realizado no comércio local do município de Aracaju -SE, ao avaliarem a qualidade microbiológica de 30 amostras de açaí pasteurizadas de três diferentes marcas, Almico et al (2018), identificação P2, relataram a presença de coliformes totais em amostras de apenas uma marca, apresentando 2,32 x 10 0 NMP/g, contagem abaixo do limite máximo preconizado.…”
Section: Coliformes Totaisunclassified